An Administrative Law Dilemma from Taxing the Economic Presence in Cloud Computing Post-Constitutional Court Decision in Indonesia - Syabina, Andi Firyani; Masum, Ahmad; Yunus, Ahsan; Ruslan, Achmad (Administrative and Environtmental Law Review, 2026)
The expansion of the digital economy, particularly cloud computing, has exposed structural limitations in Indonesia’s Income Tax framework, which remains based on physical presence. In response, the government introduced the concept of significant economic presence as a new taxation basis, yet this reform was undermined when the Constitutional Court annulled its statutory foundation. Using a normative conceptual approach, this research moves beyond problem identification by proposing a concrete legislative solution to the resulting regulatory vacuum. Its contribution lies in offering a legal reconstruction model that reinstates the significant economic presence nexus within the permanent Income Tax Law by redefining the digital economy and Permanent Establishment to include quantitative indicators such as revenue thresholds and user participation. The study concludes that harmonizing Income Tax regulations with constitutional principles would strengthen legal certainty and improve Indonesia’s capacity to tax digital services such as cloud computing.